Acinetobacter nosocomialis: Defining the Role of Efflux Pumps in Resistance to Antimicrobial Therapy, Surface Motility, and Biofilm Formation - Knight, Daniel B.; Rudin, Susan D.; Bonomo, Robert A.; Rather, Philip N. (Frontiers in Microbiology, 2018)
Abstract. Acinetobacter nosocomialis is a member of the Acinetobacter calcoaceticus-Acinetobacter baumannii (ACB) complex. Increasingly, reports are emerging of the pathogenic profile and multidrug resistance (MDR) phenotype of this species. To define novel therapies to overcome resistance, we queried the role of the major efflux pumps in A. nosocomialis strain M2 on antimicrobial susceptibility profiles. A. nosocomialis strains with the following mutations were engineered by allelic replacement; ΔadeB, ΔadeJ, and ΔadeB/adeJ). In these isogenic strains, we show that the ΔadeJ mutation had a significant role in beta-lactam, beta-lactam/beta-lactamase inhibitors, chloramphenicol, monobactam, tigecycline and trimethoprim resistance. In contrast to that seen in A. baumannii, the ΔadeB mutation had only a minor role in resistance to certain beta-lactams, rifampicin and tigecycline. In addition, the ΔadeJ mutation had a significant impact on surface motility and a minor role in biofilm formation. Our results indicate that the efflux pump, AdeIJK, has additional roles outside of antibiotic resistance in A. nosocomialis.